Pengaruh Fee Audit, Tenure Audit Dan Rotasi Audit Terhadap Kualitas Audit Jakarta - Muhammad Fakhri Putra Prima; Juniati Gunawan (Journal of Creative Student Research, 2024)
This research aims to find out the effect of audit fees, audit tenure, audit rotation on audit quality in Jakarta. This type of research is quantitative research. The data used in this research is primary data. The number of samples is 100 respondents. The population in this research is auditors including partners at KAP in the Jakarta area, with a sample of 100 respondents. Data collection uses the questionnaire method. The data analysis method uses multiple linear regression and uses the SPSS version 26 application, where it is concluded that each variable Audit Fee, Audit Tenure and Audit Rotation has an effect on audit quality. Simultaneously, Audit Fee, Audit Tenure and Audit Rotation influence audit quality.